2013
DOI: 10.5114/pjp.2013.39331
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian small cell carcinoma of hypercalcemic type – evidence of germline origin and smarca4 gene inactivation. a pilot study

Abstract: Ovarian tumors from two patients, compatible by histological and immunohistochemical criteria with small cell carcinoma of hypercalcemic type (SCCHT) (WT1+, EMA dispersed+, synaptophysin+ or dispersed+), were extensively sampled in order to find clues to their histogenesis. Subsequently, small foci of immature teratoma were found in both of them (in 1/122 and in 3/80 tumor sections). In one case, microfoci of yolk sac tumor were also present within the teratoma area as well as in the background of the small ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
94
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(95 citation statements)
references
References 14 publications
1
94
0
Order By: Relevance
“…Stringent variant-calling methods were used to identify single-base substitutions and indels (see the Online Methods and Supplementary Table 2 for a list of the variants identified in each tumor). SMARCA4 , a gene previously implicated in SCCOHT 7 , was the only recurrently mutated gene, bearing inactivating mutations in six of nine tumors and in BIN-67 cells (Table 1). Two tumors harbored two mutations each in SMARCA4 , suggesting biallelic inactivation.…”
mentioning
confidence: 99%
“…Stringent variant-calling methods were used to identify single-base substitutions and indels (see the Online Methods and Supplementary Table 2 for a list of the variants identified in each tumor). SMARCA4 , a gene previously implicated in SCCOHT 7 , was the only recurrently mutated gene, bearing inactivating mutations in six of nine tumors and in BIN-67 cells (Table 1). Two tumors harbored two mutations each in SMARCA4 , suggesting biallelic inactivation.…”
mentioning
confidence: 99%
“…Furthermore, the recently observed clustering of small cell carcinoma of the ovary, hypercalcemic type (SCCOHT; [8]) in families with malignant rhabdoid tumors suggests a link between SCCOHT and the SWI/SNF pathway [9,10]. This observation is strengthened by the fact that some of the SCCOHT cases display frank rhabdoid phenotype (so-called large cell variant [11]).…”
Section: Introductionmentioning
confidence: 86%
“…1, 2 Several recent studies have reported a high frequency of inactivating, predominantly nonsense, splice-site or frameshift SMARCA4 (also known as BRG1 ) mutations in these tumors, which lead to loss of protein expression. 36 No other recurrent mutations were detected in SCCOHT in these studies. 4 …”
Section: Introductionmentioning
confidence: 55%